Depreciation by Probability-Life. - Jen, Frank C.; Huefner, Ronald J. (The Accounting Review, 1970)
The article demonstrates that the current procedure of estimating asset life for depreciation purposes is inadequate and advocates the use of the entire probability distribution of asset life. After reviewing certain current depreciation procedure, it discusses the probability-life approach to depreciation and its implications for the inter-temporal allocation of depreciation expense. The effect of depreciation adjustment under both the traditional mean-life and probability-life approaches is analyzed. Criteria that can be used to choose between mean-life and probability-life are then discussed. Finally, consideration is given to the application of the probability-life concept to group depreciation and also to accelerate methods. The article also says that the choice of a depreciable life for an asset requires an estimate of the length of time that the asset will provide its services to the company. Since an uncertain future is being estimated, one is faced with the problem of estimating the probability distribution of the asset life.